1993
DOI: 10.1101/gad.7.7a.1111
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cell proliferation by p107, a relative of the retinoblastoma protein.

Abstract: The cellular protein p107 shares many structural and biochemical features with the retinoblastoma gene product, pRB. We have isolated a full-length cDNA for human p107 and have used this clone to study the function of p107. We show that, like pRB, p107 is a potent inhibitor of E2F-mediated trans-activation, and overexpression of p107 can inhibit proliferation in certain cell types, arresting sensitive cells in G1. Several experiments, however, showed that growth inhibition by pRB and p107 did not occur through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
576
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 508 publications
(600 citation statements)
references
References 63 publications
(84 reference statements)
23
576
1
Order By: Relevance
“…RB is the founder of the RB family of genes and proteins, since two other factors structurally and functionally related, namely p107 (RBL1) (Ewen et al, 1991;Zhu et al, 1993) and Rb2/p130 (RBL2) (Hannon et al, 1993;Li et al, 1993;Mayol et al, 1993), have been subsequently identified. The RB family proteins share a considerable structural homology, primarily at the level of the 'pocket' domain, a complex structure subdivided in A-domain, spacer and B-domain.…”
Section: And References Therein)mentioning
confidence: 99%
See 3 more Smart Citations
“…RB is the founder of the RB family of genes and proteins, since two other factors structurally and functionally related, namely p107 (RBL1) (Ewen et al, 1991;Zhu et al, 1993) and Rb2/p130 (RBL2) (Hannon et al, 1993;Li et al, 1993;Mayol et al, 1993), have been subsequently identified. The RB family proteins share a considerable structural homology, primarily at the level of the 'pocket' domain, a complex structure subdivided in A-domain, spacer and B-domain.…”
Section: And References Therein)mentioning
confidence: 99%
“…The RB family proteins share a considerable structural homology, primarily at the level of the 'pocket' domain, a complex structure subdivided in A-domain, spacer and B-domain. A-and B-domains are the most conserved among the three RB proteins and are involved in common functional characteristics (Paggi et al, 1996;Mulligan and Jacks, 1998), the most relevant one being the ability to control the cell cycle by negative modulation of the transition between the G1 and S phases (Goodrich et al, 1991;Zhu et al, 1993;Claudio et al, 1994;Starostik et al, 1996). To perform this task, these 'pocket proteins' utilize mechanisms mostly related to inactivation of transcription factors (Kouzarides, 1995), such as those of the E2F family (Cao et al, 1992;Helin et al, 1992Helin et al, , 1993Shirodkar et al, 1992;Beijersbergen et al, 1994;Hijmans et al, 1995;Sardet et al, 1995;Hurford et al, 1997), that promote the cell entrance into the S phase (Ewen, 1994;Weinberg, 1995;Paggi et al, 1996;Mulligan and Jacks, 1998).…”
Section: And References Therein)mentioning
confidence: 99%
See 2 more Smart Citations
“…The E2F transcription factor, in turn, is regulated by the retinoblastoma family of growth-inhibitory proteins. This family consists of three members: the retinoblastoma protein (pRb) and the related p107 and p130 (Hannon et al, 1993;Li et al, 1993b;Zhu et al, 1993;Weinberg, 1995). Collectively, these proteins are known as the`pocket' proteins, as they have a domain, named the pocket, with which they can bind and inactivate several cellular proteins.…”
Section: Introductionmentioning
confidence: 99%